A single 1,500 m freestyle at maximal speed decreases cognitive function in athletes - Lai, Zhijie; Huang, Weiwei; Lin, Wentao; Weng, Xiquan; Mao, Yuheng; Xu, Guoqin (Frontiers in Psychology, 2023)
Physical exercise can improve cognitive function, and the degree of impact on cognitive function is related to exercise modality, intensity and duration. However, few studies were found on the effects of competitive sports on cognitive function. The 1500-m freestyle is the longest poolbased swimming event in the Olympic Games. This study explored the effects of 1500-m freestyle at maximal speed on athletes' cognitive function and analyzed the potential mechanism of cognitive function reduction in freestyle at maximal speed from the perspective of hemoglobin oxygenation difference (Hbdiff). Thirteen male university swimmers were required to undergo a 1500-meter freestyle at maximal speed competition. The relevant indicators, including cognitive function and freestyle at maximal speed, before and after the competition were tested and analyzed. Cognitive function was assessed using the Schulte grid test (SGT), the trail making test (TMT) and the digit span test (DST). The neurobiological characteristics of cognitive function, such as the prefrontal cortex (PFC), response time (RT) and accuracy rate (ACC), were tested using functional nearinfrared spectroscopy (fNIRS). The results showed a significant decrease in scores for SGT, TMT, and digit span test-backward (DST-B) (p < 0.01). Oxygenated hemoglobin (Oxy-Hb) concentrations in the right frontopolar area (R-FPA) of brain channels 8 (p < 0.01) and 9 (CH8, 9) (p < 0.05), the right dorsolateral prefrontal cortex (R-DLPFC) CH10 (p < 0.05) and the middle dorsolateral prefrontal cortex (M-DLPFC) CH18 (p < 0.01) were significantly altered, and the right area of the brain was activated. The total Oxy-Hb concentrations in the ROIs of R-FPA, R-DLFPC, and M-DLFPC were changed significantly (p < 0.01). In conclusion, the exhaustive performance of a 1500meter freestyle event resulted in both physical fatigue and a decline in cognitive function. This decline may be attributed to the activation of specific regions of interest, namely the FPA, DLPFC, and M-DLPFC, within the prefrontal cortex (PFC), as well as alterations in functional connectivity.